Implementation of the TOPSIS Method in a Website-Based Hospital Employee Performance Evaluation System to Improve Assessment Objectivity - Izzah Farikhah; A. Aviv Mahmudi; Fajar Sodiq (Jurnal Teknologi Informatika dan Komputer, 2026)
The rapid development of information technology has led to transformation in various fields, one of which is the health sector. Digitalization encourages public service institutions to adapt to new systems to increase efficiency, speed, and accuracy of services in hospitals. This study is based on the manual employee performance evaluation process at Bhina ​​Bhakti Husada Hospital, which causes the assessment to take longer, is prone to errors, and has the potential to cause bias between units or assessors. This study aims to develop a Website-based Decision Support System using the TOPSIS Method. The study was conducted using data collection methods through observation, interviews, and literature studies while implementing Rapid Application Development (RAD) for system development. The TOPSIS method is used to calculate preference values ​​based on ten assessment criteria. The results of the study show that the system is able to calculate employee ratings automatically, display a performance dashboard, and generate reports in PDF format. The system can improve the efficiency of assessment time, maintain objectivity through standardized criteria weights, while providing different access for admins, assessors, employees, and leaders. The results of the study are also in line with previous studies that state the TOPSIS Method is effective for performance assessment, this study also provides new contributions through the integration of the TOPSIS Method in a real-time website-based system. The system can be developed with several other features for the benefit of Hospital Management to make performance more flexible.